Bay' al-Murabahah: Mendudukkan Kembali Posisinya dalam Perbankan Syari’ah - Luhur Prasetiyo (Justicia Islamica, 2012)
Nowadays, Mura>bah}ah transaction becomes the most popular product which shari>’ah banking uses to sell its assets for amount of reasons. Total amount of shari>’ah banks store and transact their assets (fund) in mura>bah}ah system. The reason is that this product has not only small risk but also ease to manage related to muz}a>rabah and musha>rakah system. In the other hand, Many people don’t understand mura>bah}ah mechanism precisely. They often think that mura>bah}ah mechanism is as credit as well. It is, in fact, that mura>bah}ah system is a cash transaction which shari>’ah banks have. This paper is to elaborate mura>bah}ah system as a product of shari>’ah banking.